Characterization of the fungitoxic activity on Botrytis cinerea of the aristolochic acids I and II. (1st January 2019) - Melo, R.; Sanhueza, L.; Mendoza, L.; Cotoras, M.
Abstract: The fungitoxic effect of aristolochic acids I and II on mycelial growth and conidial germination of Botrytis cinerea was analysed. Aristolochic acid I had a higher effect on mycelial growth of B. cinerea than aristolochic acid II with IC50 value of 18·7 and 57·0 μ g ml −1, respectively. These compounds did not affect the conidia germination. Also, the effect of both compounds on DNA and plasmatic membrane integrity of B. cinerea was studied. Only aristolochic acid II was able to cause damage to the integrity of the plasmatic membrane. When the fungus was incubated with a mixture of these compounds, degradation of DNA was observed. Finally, biotransformation products were not detected in the culture broth when B. cinerea was incubated in the presence of the aristolochic acids. Studies of structural characteristics that increase the antifungal effect of compounds against B. cinerea will permit to design new molecules to control this phytopathogenic fungus. Significance and Impact of the Study: The fungitoxic effect on Botrytis cinerea of aristolochic acids I and II was characterized. The only structural difference among these compounds is a methoxy group at carbon 8. However, despite their structural similarity, the fungitoxic effect of aristolochic acid I was higher than the effect of aristolochic acid II. This result suggests that the methoxy group is important for the fungitoxic activity of these compounds on B. cinerea .